Crisis Management During COVID-19 (International Journal of Innovative Research in Engineering & Management, 2021)
The social environment and crisis management approaches are  highlighted in this article. Depending on 1000 conversations  involving corporate leaders in Swedish small or medium-sized  firms, users are searching into disaster management. They're  curious about the social conditions in which firm executives  respond to crises, as well as the working styles they use. Almost  majority of firms in this survey don't have a disaster  management in the organization and rather than deal with  problems as they arise. Few businesses maintain their crisis  plans up to date on even a regular basis, or only around half of  those that do believe it was helpful in dealing with both the  coronavirus COVID-19 situation. According to the findings,  Swedish Small medium enterprises (SMEs) seem to be reliant  on a developing procedure in which decision are made mostly  on gut feelings. The organizations in our sample that saw  significant drops in revenue as a consequence of the COVID 19 problem, on the other hand, claim to take a more organized  and rational approach to their job, based on reports and  documentation. The research adds to our knowledge of how  disaster response operates. A contingency/crisis strategy, but in  the other side, appears to be critical, but there's enough proof  that all these strategies or routines must need the least amount  of money or time to execute in order for Businesses being well  ready for future calamities.
Keywords: Businesses; Crisis Management; COVID-19; Pandemic; Small Medium Enterprises